Unveiling the Transformation: The Impact of Teaching Internships in Thai Schools on Pre-Service Teachers' Professional Development - Aisyah; Fitriah; Rakhmawati; Mapa, Ahlam Hasan (Center for the Research and the Community Service, Islamic Institut of Hasanuddin Pare - Kediri, 2023)
Being an effective teacher requires teaching experience and practical knowledge about the classroom. The knowledge can be obtained from classroom lectures and teaching practices can be learnt by having internship programs at schools and the community. This study aims to uncover the transformation of Indonesian pre-service teachers to their Professional Development during their participation in the international internship program in Thailand. Qualitative method was carried out to understand participants’ experience and benefits of the program. The study interviewed seven pre-service teachers who were selected enrolling in the program. The finding indicated that international teaching internships the participants involved help improve their professional development. They believed that there were three aspects affecting their professionalism, namely, pedagogical skills, language competencies, and life skills. This present study highlights that participating in teaching internships is useful for students’ professional development. As they will be a teacher, having teaching practice will provide students with the opportunity to apply what they have learnt to the real-world teaching situation, and this will be meaningful for their profession.